IN VITRO ANTIMICROBIAL POTENTIAL OF ROOT EXTRACTS OF THE MEDICINAL PLANT SPECIES, EMELIA SONCHIFOLIA (LINN.) DC. - K., THENMOZHI; M., SARADHA; S., MANIAN; S., PAULSAMY (Asian Journal of Pharmaceutical and Clinical Research, 2013)
In the present investigation, evaluation of antimicrobial potential of the methanolic root extracts (25, 50, 75 and 100mg/mL) of the plant species, Emelia sonchifolia (Asteraceae) was carried out against certain Gram-positive bacteria (Staphylococcus aureus, Bacillus cereus, B. subtilis and Streptococcus faecalis,) and Gram-negative bacteria (Salmonella typhi, Pseudomonas aeureginosa, Shigella dysenteriae and Klebsiella pneumoniae) and fungi (Aspergillus niger, Candida albicans, Tricoderma viride, Azospirillum lipoferum and Mucor racemosus) by detecting the zone of inhibition using disc diffusion method. The methanolic root extracts possess significant antimicrobial activity at 100mg/mL against the tested bacteria and fungi. The minimum inhibitory concentration (MIC) of the extracts ranged from 400 to1000Âµg/mL. Therefore, the result obtained suggests that the root extracts exhibited effective target based molecular drugs against dreadful microorganisms. Keywords: Emelia sonchifolia, Asteraceae, Antimicrobial activity